Moral Rules, Self-Control, and School Context: Additional Evidence on Situational Action Theory from 28 Countries - Kafafian, Matthew (Journal of quantitative criminology, 2022)
Objectives The goal of the study is to address several voids in the literature investigating Situational Action Theory (SAT) by: (1) testing the role of parenting as a precursor to individual moral rules and self-control; (2) investigating the interplay between personal moral rules, self-control, and rules of school settings; and (3) exploring the generalizability of these theoretical links across western and nonwestern country clusters. Methods Using unique data from the third iteration of the International Self-Reported Delinquency Survey (ISRD-3) of 28 different countries, this investigation puts SAT to the test in school settings by estimating a series of two-level mixed effect negative binomial linear regression models to assess the effects of SAT-relevant individual and school-level predictors on offending. Results The results suggest a moderately strong performance of SAT in western and nonwestern countries. Specifically, parenting acts as a partial precursor to individual moral rules and self-control. Furthermore, some SAT-relevant predictors are equally potent as crime predictors across western and nonwestern countries. However, the effects of moral rules significantly differ across western and nonwestern country clusters. Moral rules also appear to interact significantly with self-control and a number of contextual factors in their effects on delinquency. Conclusions The results of the study point to the cultural generalizability of SAT but warrant further investigation as some differences in the findings across clusters exist.